Ответы и объяснения

2014-01-03T19:55:16+00:00

2a+27b²-12a²-3b     (27b²-12a²)+(2а-3b)    3(9b²-4a²)+(2а-3b)     

---------------------- =  --------------------------  = -------------------------   = 

2a-3b                             2a-3b                             2a-3b                                      

3((3b-2a)(3b+2a))+(2а-3b)   (2a-3b)(-3(3b+2a)+1)     (2a-3b)(-9b-6a+1)
----------------------------------- =  --------------------------  = -------------------------   = 

             2a-3b                             2a-3b                             2a-3b      

=-9b-6a+1           Вроде так.